Lowered progesterone metabolite excretion and a variable LH excretion pattern are associated with vasomotor symptoms but not negative mood in the early perimenopausal transition: Study of Women's Health Across the Nation. (May 2021) - McConnell, Daniel S.; Crawford, Sybil L.; Gee, Nancy A; Bromberger, Joyce T.; Kazlauskaite, Rasa; Avis, Nancy E.; Crandall, Carolyn J.; Joffe, Hadine; Kravitz, Howard M.; Derby, Carol A.; Gold, Ellen B.; El Khoudary, Samar R.; et al.
Highlights: We measured daily vasomotor symptoms, and urinary hormone levels: follicle stimulating hormone (FSH), luteinizing hormone (LH), pregnanediol glucuronide (PdG) and estrone conjugates (E1C). A variable pattern of LH and negative LH feedback were the hormone patterns most strongly associated with increased vasomotor symptoms. No hormone pattern was significantly related to negative mood. Abstract: Objective: The menopausal transition is characterized by progressive changes in ovarian function and increasing circulating levels of gonadotropins, with some women having irregular menstrual cycles well before their final menstrual period. These observations indicate a progressive breakdown of the hypothalamic-pituitary-ovarian axis often associated with an increase in menopausal symptoms. Relationships between vasomotor symptoms (VMS) and depressed mood and sleep as well as a bidirectional association between VMS and depressed mood in mid-life women have been reported, but the endocrine foundations and hormone profiles associated with these symptoms have not been well described. Our objective was to determine the relationship between daily urinary hormone profiles and daily logs of affect and VMS during the early perimenopausal transition. Study Design: SWAN, the Study of Women's Health Across the Nation, is a large, mutli-ethnic, multisite cohort study of 3302 women aged 42–52 at baseline, designed to examine predictors of health and disease in women as they traversed the menopause. Inclusion criteria were: an intact uterus and at least one ovary present, at least one menstrual period in the previous three months, no use of sex steroid hormones in the previous three months, and not pregnant or lactating. A subset (n = 849) of women aged 43–53 years from all study sites in the first Daily Hormone Study collection were evaluated for this substudy. Outcome Measures: We measured daily VMS, and urinary hormones: follicle stimulating hormone (FSH), luteinizing hormone (LH), pregnanediol glucuronide (PdG) and estradiol (estrone conjugate, E1C). Results: A variable pattern of LH and negative LH feedback were the hormone patterns most strongly associated with increased VMS. In contrast, no hormone pattern was significantly related to negative mood. Conclusion: Fluctuations of LH associated with low progesterone production were associated with VMS but not negative mood, suggesting different endocrine patterns may be related to increased negative mood than to the occurrence of VMS.